Integrated Photonic and Electronic Circuits Using CMOS Technology - Abbas B. Noori (Genius Journals, 2023)
A massive growth is about to begin in the optical components sector, which will reorganize its business procedures and guarantee its financial success over the next three decades.
Keywords: EPIC, Optical Filters, Waveguides